Peasant struggle, socio-environmental conflict and multi-territoriality: a possible international airport in Palmar de Osa, Costa Rica - Mora Calderón, José Antonio (2024)
This article aims to analyze a socio-environmental conflict stemming from the potential construction of an international airport in the Palmar Sur Farms of Osa, Puntarenas, Costa Rica. The analysis was conducted within the framework of Human Geography, specifically focusing on the concepts of territorial typologies and multi-territorialities. Methodologically, the information collection techniques were qualitative, consisting of documentary review, interviews with key individuals, and fieldwork. Various territorial projects in the area were examined in relation to the international airport project, emphasizing the role of peasant struggle, facilitated by the Peasant Struggle Organization for Our Lands, in asserting their claim to peasant territory. A key conclusion drawn is that multi-territorialities involve power dynamics among socio-territorial actors such as the State, corporations, and peasant communities. Understanding peasant resistance as another territorial project opposing a mega-territorial project, such as airport construction, is deemed essential. Key words: Multiterritorialities, Airport, Peasantry, Southern Zone, Palmar, Farms, Human Geography.